559Health of Aboriginal children in Western Australia: Do grandparents matter?. (2nd September 2021) - Gibberd, Alison; Preen, David; Shepherd, Carrington; Eades, Sandra; McNamara, Bridgette
Abstract: Background: Studies of select populations (e.g. pre-industrial or subsistence farming populations) suggest that children with living maternal grandmothers (MGMs) had improved survival. It is unknown if this holds for child health more generally or in Australian Indigenous communities, where care of children is commonly shared by family members. We examined associations between the health of young Aboriginal Western Australians and their grandparents. Methods: Birth, death, inpatient and emergency department records of Aboriginal infants born 2000-2013 in WA and their grandparents were linked. Grandparents were classified as 'healthy' (alive with Charlson comorbidity index score of 0 or 1), 'unhealthy' (alive with a score of ≥ 2), or dead when the child was born. Results: Among the 27, 425 children, mortality by age 2 was lower with healthy grandparents (e.g. 11 deaths per 1000 live births with healthy MGMs; 22 with unhealthy; 16 with dead MGMs) and acute healthcare contacts were fewer (e.g. 13% with healthy MGMs spent ≥7 days in hospital by age 2 vs 19% with unhealthy or dead MGMs). However, healthcare contacts were generally unrelated to grandfathers. Outcomes were better for children with 2 living grandmothers (e.g. 1.5% with 2 grandmothers were discharged against medical advice in 2 years; 2.7% with 1 grandmother; 3.7% with none). Conclusions: Children with healthy grandmothers had lower mortality and morbidity. These associations are unlikely to be due to genetic or environmental factors, as they are weaker/missing for grandfathers. Key messages: Good health among older Aboriginal people may also benefit the health of subsequent generations.